Creating greener citizens: political liberalism and a robust environmental education - Stevens, David (Springer, 2014)
Proponents of environmentalist views often urge the teaching of such views and the inculcation of ‘green’ values within the educational curriculum of schools as a key component of achieving their ends. It might seem that modern versions of political morality that refuse to take a stance on controversial questions—religious, ethical, philosophical—or eschew appeal to perfectionist doctrines, such as Rawlsian political liberalism, are beset by a particularly acute difficulty in this regard. To the extent that environmentalist views embody claims about ethical matters such as how individuals should live their lives, they fall foul of this version of political morality. This article evaluates the resources available to political liberalism to respond to the challenge of bringing the teaching of green values and virtues within the national curriculum. It argues that environmental concerns differ in morally important ways from other ethical, philosophical, and religious views that are typically off-limits to political liberalism. Much that passes as green ideals are not simply a conception of the good life in the manner that religious views, for example, are. Rather, many environmental goods are crucial to the realisation of socioeconomic justice and therefore escape the requirement of state neutrality on endorsing the truth or importance of their role. A minimal political liberal education includes teaching about justice-based concerns as part of a compulsory national curriculum.